Yield potential - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1985)
Although lateness will continue to be sought as a route to absolute max. yield in the CIAT Bean Program, overall work on yield potential is also being directed toward other groups of materials including medium- and large-seeded lines and early maturing lines. It has consistently been observed that yields of large-seeded bush beans are lower than those of small-seeded ones. Later maturing lines are expected to result in increased yield potential and while early lines are of interest for a range of reasons, yield stability is perhaps the most important. (CIAT)